A multi-level approach to examining food security, race, academic performance, and post-secondary confirmation in a Toronto high school cohort, 2011-2014. Issue 1 (2nd January 2021) - Robson, Karen; Pullman, Ashley; Anisef, Paul; Brown, Robert S.; Maier, Reana
ABSTRACT: The following study examines how a class-based measure of food security was associated with high school grades and later post-secondary enrollments by self-identified race. We use multilevel regression to analyze data merged among the 2011 Toronto District School Board Student Census, administrative records, and college and university application information. Statistical interaction terms examine if food security is differentially associated with educational outcomes by race. The results show there is a positive association between food security and Grade 12 grades as well as post-secondary confirmation. This association, however, varies by self-identified race. Food security is less important for the academic success of East Asians students compared to Whites. For Black students, food security has a comparably flat association with grades, but reduces their likelihood of having a rejected post-secondary application. The findings highlight that food security, as a class-based resource, differentially benefits racial groups in terms of their educational outcomes.